Dialogue, ethics, economy. The application of dialogue in management (in the context of business ethics in the German-speaking area) - Szulczewski, Grzegorz (Annales. Etyka w Życiu Gospodarczym, 2019)
The article names the conditions that a conversation has to fulfill in order to become a dialogue. The author undertakes to present the philosophy and ethics of dialogue, which were established based on the concept of dialogue. Its representatives include Jürgen Habermas and Karl-Otto Apel. Next, on the example of German business ethics, it is demonstrated how the philosophy and ethics of dialogue could become the foundation of the Republican economic ethics, developed by Peter Ulrich, and corporate ethics, put forward by Horst Steinmann. In the author’s opinion, they may prove useful in developing a new version of business ethics, formed upon reflection about experiences of the financial and economic crisis that began in 2008 and the effects of which are visible to this day.